AKTIVITAS ANTIBAKTERI ASAP CAIR DARI LIMBAH TEMPURUNG KELAPA TERHADAP DAGING KELINCI ASAP - Pramono Sasongko; Wahyu Mushollaeni; Herman Herman (Universitas Tribhuwana Tunggadewi, 2014)
Rabbit meat is the alternative of protein source with high nutrition value, but susceptible to contamination by spoilage bacteria. The application of liquid smoke coconut shell based could be the of developed method to overcome the problems of bacterial contamination. This study was conducted to determine the effect of immersion liquid smoke coconut shell to the total number of bacteria in smoked rabbit meat. Treatment of various concentrations of liquid smoke were used in the production of smoked rabbit meat were 0% 1%, 1.5%, 2% and 2.5% (v / v). Based on the analysis results, it can be concluded that the use of 2% liquid smoke concentration can provide an effective antibacterial effect. The total number of bacteria based on the method of Total Plate Count shows this concentration can decrease the amount of bacteria up to 99.9% with the results of 0 CFU / g